The way forward for Building Information Modelling (BIM) for contractors in Malaysia - Mohd Harris, .; Adi Irfan, Che Ani; Ahmad Tarmizi, Haron; Afifudin Husairi, Husain (Construction Research Institute of Malaysia, 2014)
Implementation of Building Information Modelling (BIM) in the Malaysian Architectural, Engineering, and Construction (AEC) industry is a methodology of practice that aims at shifting ways of thinking and working processes. This paper seeks to investigate the barriers, potential solutions and benefits of implementing BIM for contractors in Malaysia. The data to support this research was gathered from through a collaborative workshop between the Construction Industry Development Board (CIDB), Malaysia and Universiti Teknologi MARA (UiTM), conducted in June 2013 to assess the barriers, potential solutions and benefits of BIM implementation in Malaysia, specifically among contractors. The findings of this research highlighted 61 issues raised by the participants during the workshop. Additionally, the study revealed that some organisations resist change or are still not ready to adopt BIM as a tool in their projects. This paper offers practical recommendations on the two main issues; i.e. people and technology needed to be addressed, besides the continuous government support programs and serious enforcement policies and regulations which are inevitable.